MAJOR CONTRIBUTIONS OF PROMINENT MUSLIM SCHOLARS DURING THE GOLDEN AGE OF ISLAM (PANGEEA, 2025)
The Golden Age of Islam saw unprecedented advances across diverse fields led by eminent Muslim intellectuals and scientists. This paper examines the seminal contributions of thirteen prominent Muslim scholars from the 8th to 15th centuries CE who played pioneering roles in history, geography, mathematics, astronomy, optics, medicine, engineering, and other domains. Their groundbreaking work formed the foundations of modern disciplines while stimulating further growth of knowledge globally.
Keywords: Islamic Golden Age; Muslim scholars; mathematics; astronomy; medicine; engineering